Influencing factors of home hospice care needs of family caregivers of the older adult with chronic diseases at the end of life in China: a cross-sectional study - Lei Wang; Yaru Li; Rui Zhao; Jiangxu Li; Xiangru Gong; Hongyu Li (Frontiers Media S.A., 2024)
IntroductionWith increased life expectancy in the Chinese population coupled with chronic disease the care needs of people at the end of life are attracting much attention. Home hospice care can help the dying older adult achieve comfort and maintain their dignity at home. However, dying at home means great responsibility and challenge for family caregivers, and there are many unmet needs. The study aimed to investigate the home hospice care needs of family caregivers of older adult people with chronic diseases at the end of life in China, and to analyze the influencing factors of home hospice care needs of caregivers.MethodsIn this cross-sectional study, from May to September 2023, 4 community health service centers were selected by stratified sampling from seven administrative districts in Jinzhou City, Liaoning Province, where home hospice care was piloted. Then 224 family caregivers were selected from the communities of seven community service centers by simple random sampling method. A general information questionnaire and the home hospice care needs questionnaire developed by our research group were used to investigate. Univariate analysis was used to compare the differences in the scores of different characteristics, and the factors with significant differences were selected for multivariate linear regression analysis to determine the final influencing factors.ResultsThe total score of hospice care needs of family caregivers was 121.61 ± 15.24, among which the end-of-life knowledge need dimension score was 24.04 ± 2.71, the highest score index was 80.13%, while the symptom control need score was 15.58 ± 3.39, the lowest score index was 62.32%. In addition, Caregivers with caregiving experience, dying older adult with longer disease duration, and dying older adult with higher levels of education were the factors influencing the total need for home hospice care among family caregivers, with a variance explained of 22.7%.DiscussionThe needs of family caregivers of the terminally ill older adult are high, and healthcare professionals should implement services to meet their multidimensional needs and improve the quality of care according to the factors affecting their needs.